The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1073/pnas.1205894109
|View full text |Cite
|
Sign up to set email alerts
|

Memory CD4+T-cell–mediated protection depends on secondary effectors that are distinct from and superior to primary effectors

Abstract: Whether differences between naive cell-derived primary (1°) and memory cell-derived secondary (2°) CD4+ T-cell effectors contribute to protective recall responses is unclear. Here, we compare these effectors directly after influenza A virus infection. Both develop with similar kinetics, but 2° effectors accumulate in greater number in the infected lung and are the critical component of memory CD4+ T-cell–mediated protection against influenza A virus, independent of earlier-acting memory-cell helper functions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
112
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(125 citation statements)
references
References 49 publications
12
112
1
Order By: Relevance
“…Consistent with this possibility that effector molecules secreted by primary and secondary effector CD4 ϩ T cells are distinct, comparative microarray analysis of the two subsets revealed approximately 450 differentially expressed genes (90). The signaling pathways between the two CD4 ϩ T cell effector types were also found to be different (90). Another recent study also demonstrated how the innate immune response was specifically modified for enhanced protection by memory T cells in both a systemic and a mucosal model of recall response (91).…”
Section: Memory In the Innate Immune Compartmentmentioning
confidence: 57%
See 1 more Smart Citation
“…Consistent with this possibility that effector molecules secreted by primary and secondary effector CD4 ϩ T cells are distinct, comparative microarray analysis of the two subsets revealed approximately 450 differentially expressed genes (90). The signaling pathways between the two CD4 ϩ T cell effector types were also found to be different (90). Another recent study also demonstrated how the innate immune response was specifically modified for enhanced protection by memory T cells in both a systemic and a mucosal model of recall response (91).…”
Section: Memory In the Innate Immune Compartmentmentioning
confidence: 57%
“…In a recall response, the differential interaction could lower the activation threshold of the innate cells and allow them to rapidly upregulate their antimicrobial effector response. Consistent with this possibility that effector molecules secreted by primary and secondary effector CD4 ϩ T cells are distinct, comparative microarray analysis of the two subsets revealed approximately 450 differentially expressed genes (90). The signaling pathways between the two CD4 ϩ T cell effector types were also found to be different (90).…”
Section: Memory In the Innate Immune Compartmentmentioning
confidence: 64%
“…Whether the provision of help by peptide-primed CD4 memory leads to more rapid clearance and protection is unclear. There are many effector functions of CD4 T cells that facilitate protection from influenza virus infection, including potentiation of the early innate response and direct cytotoxicity (6,24,38,80,81; reviewed in references [82][83][84][85]. We expect that the latter two functions of CD4 T cells may be carried out by cells reactive to peptides derived from many viral proteins, including HA, NA, NP, and M1, because these proteins are synthesized or available in many cells within the lung.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of whether CD4 frequency is predictive of a B cell response has yet to be well established though recent evidence is accumulating that suggests a close relationship (21,22). Endogenous or adoptively transferred memory CXCR5 ϩ CD4 T cells can accelerate the B cell response to a model protein antigen (23) and have also been shown to have "superior" functionality in the lymph node (LN) and lung of infected mice (24). In humans, CXCR5-expressing cells in the blood are functionally related to Tfh cells, perhaps representing the memory component of these B cell helpers (25,26).…”
mentioning
confidence: 99%
“…In lymphoid organs, secondary germinal centres are thought to be formed by reactivated IgM+ memory B‐cells, providing a blank canvas for antibody class switching relevant to the pathogen 73. In influenza virus‐infected mice, CD4 T‐cells and B‐cells can be found in clusters within the lung, and many virus‐specific B‐cells in the lung are class switched 74, 75. This suggests that germinal centres formed in ELS in peripheral tissues may follow different rules to those in lymphoid organs following re‐infection.…”
Section: Memory Cd4 T‐cells Are Found Throughout the Bodymentioning
confidence: 99%